Routine child immunizations in India during the COVID-19 pandemic - Averi Chakrabarti; Elizabeth F. Bair; Harsha Thirumurthy (Elsevier, 2023)
Disruptions in health service delivery and utilization during the COVID-19 pandemic may have caused many children worldwide to not receive vital preventative health services. We investigate the pandemic's effects on routine childhood vaccinations in India, which has the world's largest child immunization program. Using data from the Government of India's health management information system and interrupted time series analyses, we estimate district-level changes in routine child vaccinations during the pandemic relative to typical monthly vaccinations in the pre-pandemic period. Our results indicate there were significant reductions in child vaccinations during the pandemic, with declines being extremely large in April 2020 when a strict national lockdown was in place. For example, district-level administration of the final required dose in the polio series declined by about 60% in April 2020 relative to the typical monthly vaccination levels observed prior to the pandemic. Vaccinations subsequently increased but largely remained below levels observed before the outbreak of COVID-19. Additional declines in vaccinations occurred in 2021 during the second wave of COVID-19 infections in India. Heterogeneity analyses suggest that vaccinations declined the most in districts with the strictest lockdowns and in districts with low health system capacity at baseline. There is a vital need for corrective actions, such as catch-up vaccination campaigns, to limit the deleterious consequences that will arise for the children who missed routine immunizations during the COVID-19 pandemic.